2020
DOI: 10.1097/moh.0000000000000571
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid sarcoma

Abstract: Purpose of review Myeloid sarcoma; also known as granulocytic sarcoma and chloroma, often occurs concomitantly with AML, and rarely without bone marrow involvement. In this article, we review the recent literature on myeloid sarcoma, focusing on treatment approach for this rare disease, and addressing the prognostic and therapeutic role of molecular and cytogenetic aberrations. Recent findings Molecular testing and cytogenetics are important adjunct to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
64
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(71 citation statements)
references
References 56 publications
0
64
1
6
Order By: Relevance
“…Complex karyotype occurs in about 17%–39% of patients. 17 In our series, no difference for complex karyotype was observed between EMI and non-EMI patients; differently trisomy of chromosome 8, which was the most frequent cytogenetic finding, was significantly more frequent in EMI patients.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…Complex karyotype occurs in about 17%–39% of patients. 17 In our series, no difference for complex karyotype was observed between EMI and non-EMI patients; differently trisomy of chromosome 8, which was the most frequent cytogenetic finding, was significantly more frequent in EMI patients.…”
Section: Discussioncontrasting
confidence: 50%
“…22 There is no consensus on the treatment of AML patients with EMI because of the disease's rarity and the lack of randomized controlled studies. 17 In most singleinstitution series previously published, AML-like induction therapy, followed by consolidation with either chemotherapy or allo-HSCT, is the current standard of care in fit patients. 23 Kaur et al, 23 in a retrospective review of 23 patients treated for EMI, reported that the overall survival was significantly improved for patients who achieved a complete response to induction chemotherapy.…”
mentioning
confidence: 99%
“…MS is an extramedullary blast cell proliferation of one or more of the myeloid lineages, resulting in disruption of the normal architecture of the tissue in which it originates [5]. While MS is listed in the World Health Organization (WHO) as a subtype of AML, in reality it is a distinct entity that warrants further pathological and genetic analysis in an attempt to define its own WHO subclassification [6].…”
Section: Discussionmentioning
confidence: 99%
“…Primarily, MS precedes AML, or both pathologies are discovered simultaneously. MS may also present de novo, as a relapse of AML, or as a progression of a prior MDS, chronic myeloid leukemia, and other myeloproliferative neoplasms [3,5,6]. Isolated MS is extremely rare, with an overall incidence of less than 1% as compared with 2.5-9% in patients with AML [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation